Characterization of impaired beta and alpha cell function in response to an oral glucose challenge in cystic fibrosis: a cross-sectional study - Nielsen, Bibi Uhre; Mathiesen, Inger Hee Mabuza; Møller, Rikke; Krogh-Madsen, Rikke; Katzenstein, Terese Lea; Pressler, Tacjana; Shaw, James A. M.; Ritz, Christian; Rickels, Michael R.; Stefanovski, Darko; Almdal, Thomas Peter; Faurholt-Jepsen, Daniel (Frontiers in Endocrinology, 2023)
Aims The purpose of the study was to further elucidate the pathophysiology of cystic fibrosis (CF)-related diabetes (CFRD) and potential drivers of hypoglycaemia. Hence, we aimed to describe and compare beta cell function (insulin and proinsulin) and alpha cell function (glucagon) in relation to glucose tolerance in adults with CF and to study whether hypoglycaemia following oral glucose challenge may represent an early sign of islet cell impairment. Methods Adults with CF (≥18 years) were included in a cross-sectional study using an extended (-10, -1, 10, 20, 30, 45, 60, 90, 120, 150, and 180 min) or a standard (-1, 30, 60, and 120 min) oral glucose tolerance test (OGTT). Participants were classified according to glucose tolerance status and hypoglycaemia was defined as 3-hour glucose <3.9 mmol/L in those with normal glucose tolerance (NGT) and early glucose intolerance (EGI). Results Among 93 participants, 67 underwent an extended OGTT. In addition to worsening in insulin secretion, the progression to CFRD was associated with signs of beta cell stress, as the fasting proinsulin-to-insulin ratio incrementally increased (p-value for trend=0.013). The maximum proinsulin level (pmol/L) was positively associated with the nadir glucagon, as nadir glucagon increased 6.2% (95% confidence interval: 1.4-11.3%) for each unit increase in proinsulin. Those with hypoglycaemia had higher 60-min glucose, 120-min C-peptide, and 180-min glucagon levels (27.8% [11.3-46.7%], 42.9% [5.9-92.85%], and 80.3% [14.9-182.9%], respectively) and unaltered proinsulin-to-insulin ratio compared to those without hypoglycaemia. Conclusions The maximum proinsulin concentration was positively associated with nadir glucagon during the OGTT, suggesting that beta cell stress is associated with abnormal alpha cell function in adults with CF. In addition, hypoglycaemia seemed to be explained by a temporal mismatch between glucose and insulin levels rather than by an impaired glucagon response.